A review of FDM and graphene-based polymer composite - J., Mogan; L., Sandanamsamy; N. A., Halim; W. S. W., Harun; K., Kadirgama; D., Ramasamy (IOP Publishing, 2021)
Graphene is a carbon that has a unique structure that is excellent in enhancing mechanical, electrical and thermal properties. The fused deposition modelling (FDM) process is a widely used 3D printing method for its low investment and operating cost. Although the FDM process is cheaper and affordable, yet the printed parts are more fragile compare to other 3D printing methods. This paper covers about FDM process and the type of base materials and filler materials. However, the focus is mainly on ABS and graphene. The mechanical properties of ABS/Graphene polymer composite and application of ABS and graphene in the industry were also discussed. Hence, it proved that graphene enhances the properties of ABS. This study is done to improve polymer-based filaments for future references.